Theodore Boone, kid lawyer - Grisham, John (Dutton Children's Books, 2010)
In the small city of Strattenburg there are many lawyers, and thirteen-year-old Theo Boone thinks he is one of them, but his inside knowledge of the justice system means trouble when a cold-blooded killer is about to go free and only Theo can stop him.